MEMBANGUN JARINGAN WIRELESS LOCAL AREA NETWORK (WLAN) PADA CV.BIQ BENGKULU - Desmon Sharon; Sapri Sapri; Reno Supardi (UNIVED Press, 2014)
The purpose of this research is to build a wireless local area network (wlan) at CV.BIQ Bengkulu. So that it can solved network problems at CV. BIQ Bengkulu. Research method used is Network Development Method. Existing LAN will be developed into WLAN that is more flexible, effective and efficient. WLAN are built using Mikrotik RB750GL as a central server. or as central network settings. A WLAN network spreads to clients using single acces point. A WLAN solved problems at existing LAN such as geographical issues and network development. Bandwidth management and firewall used as usage policys. This network has been tested and the result are in accordance with the plan even though there are still some problems that must be overcome at the future. Advice from the author is necessary to routine maintenance so the network performance will remain well.Keywords: WLAN, Mikrotik, Bandwidth Management, Firewall